2021
DOI: 10.3390/en14082125
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Wear Mechanisms of the Components of Machines Used in Fossil Energy Resource Extraction

Abstract: The paper presents the results of tests of wear of hardened wear-resistant steels in the presence of quartz, coal and coal-mineral abrasives of a differentiated ratios of each component and in the case without abrasives. The tests were carried out on a ring-on-ring test stand. Volume loss was the parameter used to characterize the wear level. Based on the Scanning Electron Microscopy (SEM) observations, different mechanisms of surface destruction depending on the type of abrasive were found. For the quartz abr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…This resulted in the accumulation of plastic strains and stresses on the titanium surface, causing it to crack. During the 10,000-cycle test, loads are generated cyclically, and cracks may grow [59]. As a result of the final loads, the fragments of the oxide film separated to form thin patches at the interface between the sample and the wear track, and separated material particles.…”
Section: Ti G4 D Av [µM]mentioning
confidence: 99%
“…This resulted in the accumulation of plastic strains and stresses on the titanium surface, causing it to crack. During the 10,000-cycle test, loads are generated cyclically, and cracks may grow [59]. As a result of the final loads, the fragments of the oxide film separated to form thin patches at the interface between the sample and the wear track, and separated material particles.…”
Section: Ti G4 D Av [µM]mentioning
confidence: 99%
“…In their previous papers [4,[64][65][66][67][68], the authors have demonstrated that the fraction of quartz, or possibly also of the SiO2 + Al2O3 complex, in abrasive mixtures has a decisive impact on the rate of wear of wear-resistant steels. The study addressed in this paper also served to establish a relation between the wear rate and the fraction of quartz (SiO2) expressed in per cent (Figure 22).…”
Section: Discussionmentioning
confidence: 99%
“…In their studies released to date the authors have analysed the effects of quartz sand [65], coal [66], siltstones [67] as well as their mixtures with quartz sand [68] on the wear of wear-resistant steels. This body of research has allowed them to conclude that the content of low-hardness minerals in the rock material can exert a fundamental impact on the underlying damage mechanism of the steel grades in question, thereby determining the intensity of their wear.…”
mentioning
confidence: 99%
“…Wieczorek et al [ 18 ] conducted wear tests on two wear-resistant steels in the presence of a mixture of quartz and ground coal, and of coal alone. What they managed to reveal in their study (similar to the authors of [ 13 ]) was the linear impact of the quartz content on the wear of steel surfaces.…”
Section: Introductionmentioning
confidence: 99%